Potensi dan strategi pengembangan kuliner halal dalam meningkatkan pertumbuhan ekonomi di Kota Bandar Lampung - Setiawan, Ade Eko; Noviarita, Heni; Hanif , Hanif (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Lampung's economic conditions, which previously showed recovery after the passing of the crisis that hit the world economy since 2008, were hit by an epidemic in 2020, which resulted in weakening GRDP and economic growth in Lampung in general and Bandar Lampung in particular. The goal of this research is to identify the potential and strategy for developing halal culinary in order to boost economic growth in the city of Bandar Lampung. The type of research used is qualitative research with field observation techniques because the data needed or collected in this study is based on the reality that occurs in people's lives. The data sources used are primary and secondary. The results of this study concluded that the potential of the banana chip culinary tourism destination KUB Telo Rezeki All Mider Bandar Lampung City has met the standard concept of developing halal tourism. The existence of sharia tourism can support economic growth by reviving the community's creative industries. The marketing strategy implemented by the KUB Telo Rezeki Banana Chips Shop in competition is based on the 4P marketing mix strategy, namely product strategy, price strategy, place strategy, and promotion strategy, and is in accordance with the Sharia marketing concept.